Scientific Trends in Maintenance Engineering: A Bibliometric Study for Strengthening Engineering Education and Innovation (2015-2025) - Ronceros, Cristhian; Vega, Ruben (LACCEI, 2025)
Between 2015 and May 2025, research in maintenance engineering experienced steady growth, driven by technological advances in Industry 4.0. This study presents a bibliometric analysis of scientific production indexed in Scopus, using the keywords: maintenance management, maintenance 4.0, and reliability—concepts linked to digital transformation in industrial contexts. An initial set of 4,715 documents was retrieved, including articles, conference papers, books, chapters, and reviews. After applying thematic filters, 3,613 documents were selected (70.6% of the total). Italy led the scientific output with 423 publications, with Politecnico di Milano as the top institution. In Latin America, the Pontifical Catholic University of Paraná (Brazil) was the most productive. The journal Lecture Notes in Mechanical Engineering (Germany) published 113 documents. “Industry 4.0” was the most frequent keyword, and Engineering was the main subject area. English dominated as the publication language, improving global visibility. The most cited article, Predictive Maintenance in the Industry 4.0: A Systematic Literature Review, received 746 citations. The most prolific author was C. Reich (Hochschule Furtwangen, Germany), with 14 publications. The results confirm a growing trend in research on smart maintenance, rising from 24 publications in 2015 to 230 in 2025, reflecting the importance of emerging technologies in enhancing industrial efficiency.